The role of citizenship in combatting terrorism - Al-Salhi, Hanan Khaled Ibrahim Jawad (Al-Adab Journal, 2019)
The current study concerned to address these gaps in literature by identifying first , level the role of citizenship in the combating terrorism among students of the iraqi university . second , identify the significance of differences in the role of citizenship in the combating terrorism according to the school stage ( first- fourth) . To achieve the aims of the current study , the researchers created a questionnaire for the role of citizenship in combating terrorism. Two hundred students were recruited. After analyze the date statistically , the results of the current study showed that there is : A high level the role of citizenship in combating terrorism among the sample , no significant differences in the role of citizenship in combating terrorism according to the stage of study ( first - fourth).